Evaluation and Design of a Beauty Clinic's Business Model in Bandung Using the Business Model Canvas (BMC) - Gumilar, Feyzi Naufal; Hasun, Farda; Rendra, Meldi (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The XYZ Beauty Clinic in Bandung, operating since 2007, has experienced a decline in monthly revenue due to increasing competition, limited marketing, lack of product variety, outdated equipment, insufficiently trained staff, poorly implemented SOPs, and an unappealing room design. A business model evaluation and improvement are conducted using the Business Model Canvas (BMC) framework to address these issues. The process begins with data collection through interviews with business owners, customer interviews to profile customers, and direct observations. The clinic's current business model is analysed using the 7 Questions framework, while a SWOT analysis identifies strengths, weaknesses, opportunities, and threats. Based on this analysis, a new business model is formulated and translated into an updated BMC for XYZ Beauty Clinic. A verification stage ensures the proposed business logic, followed by a financial simulation to assess the feasibility and profitability of the strategies. Improvements include targeting a new market segment, particularly youth, recruiting additional doctors, and enhancing human resource quality through therapist training. The clinic should diversify its services, adding sexually transmitted disease consultations, redesigning spaces and product packaging, and leveraging TikTok and influencer partnerships for marketing. Additionally, technology-based financial management is recommended. The economic simulation predicts an incremental IRR of 65% and an NPV of IDR 111,267,697, assuming a 15% sales increase. Further validation is required to align strategies with consumer needs and ensure long-term success.Keywords: Business Model Canvas, Business Model, XYZ Beauty Clinic